(untitled) (Altre Modernità, 2011)
The purpose of this article is to develop a concrete investigation about the afro-descendants identities in nowadays Peru through the analysis of the African presence in the colonial age, focusing on different phases such as the abolition of slavery, the political independence and the statement of rights which for long time has been denied to this social class, until the actuality. Further to the outlining of the historical and social background of the afro element’s complexity in the survey of the variegated biological and cultural Peruvian mosaic, this case study focus on the today’s afro-Peruvian identity’s question, investigating about characteristics, problems and ways of interaction with the rest of the Peruvian population. Moreover, this analysis keeps track of the “negritude”, that is the afro movement, in the Peruvian art, literature and culture. Thanks to a study experience in Peru of the author, this piece offers also a picture of the current situation of afro-Peruvian communities and emphasizes the social and cultural initiatives and also political measures taken in the last years in order to assert the distinctive feature of the afro-Peruvian identity in Peru and all over the world.